Feasibility, safety, and reliability of exercise testing using the combined arm-leg (Cruiser) ergometer in subjects with a lower limb amputation - Simmelink, Elisabeth K.; Wempe, Johan B.; Geertzen, Jan H. B.; van der Woude, Lucas H. V.; Dekker, Rienk (PloS one, 2018)
Physical fitness of patients with a lower limb amputation predicts their walking ability and may be improved by physical exercise and training. A maximal exercise test is recommended prior to training in order to determine cardiovascular risks and design exercise programs. A potentially suitable ergometer for maximal exercise testing in patients with a lower limb amputation is the combined arm-leg (Cruiser) ergometer. The aim of this study was to determine feasibility, safety, and reliability of (sub)maximal exercise testing on the Cruiser ergometer in subjects with a lower limb amputation. Subjects with a lower limb amputation performed 1 submaximal exercise test and 3 maximal exercise tests on the Cruiser ergometer. Feasibility was determined by examining whether key variables such as power output, heart rate and oxygen uptake were correctly and reliably measured, by determining whether a test was a maximal aerobic performance, by studying reasons for non-completion, and by measuring gross efficiency. Safety was analyzed by recording complications, electrocardiogram results, and blood pressure. Reliability was tested by comparing the results of the second and third maximal exercise test. Seventeen subjects (14 men and 3 women) out of 21 preselected subjects completed the study. In general, the maximal Cruiser exercise test was feasible. Almost 75% of the subjects reached a maximal aerobic performance. The test was also safe because no complications occurred, although electrocardiogram and blood pressure could only be reliably recorded in most subjects just before and after the test. Reliability was good: Intraclass correlation was 0.84 for peak oxygen uptake. The Cruiser ergometer is a feasible, safe, and reliable ergometer for measuring physical fitness of subjects with a lower limb amputation.